STRATEGI PEMERINTAH INDONESIA DALAM MENINGKATKAN INDUSTRI PARIWISATA INDONESIA MELALUI VISIT INDONESIA YEAR (VIY) 2008 - Abdul Hafiz Gustiawan; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research aims to determine about how the Indonesian government strategyespecially the Ministry of Culture and Tourism in developing the tourism industry inIndonesia with the aim to attract foreign tourists so that they can compete with othercountries, especially in the region of Southeast Asia and to improve the economy ofIndonesia. author tries to describe and explain the strategy for the tourism industrymenignkatkan through the Visit Indonesia Year 2008. Sources to be presented in thisresearch is secondary sources.Sources were obtained through literature review, other books, internet, etc. Thesources analysis isqualitative analiysis. This research uses the theory of foreignpolicy with the concept of national interest which form the basis for working out astrategy. using state actors, using theory to explain how the strategy to increasetourism in IndonesiaThe Conclusion of this research is the Indonesian government strategy to improve thetourism industry through the Visit Indonesia Year 2008 has been successfully improveforeign tourists coming to Indonesia and Indonesia to promote economy.Keyword : Strategy, Visit Indonesia Year, Tourism and Foreign Policy